Pemberdayaan UMKM Pedesaan melalui Digitalisasi dan Legalitas Usaha: Studi Kasus Padukuhan Sendangtirto, Sleman - Fitri Puspasari; Hanifam Rezki Ramadhan; Maritza Zahra Setyawan; Gina Dewita; Fiant Lintang Cahyani; Hasna Nafiah Fadila (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, particularly as drivers of local economic activities and providers of employment opportunities in rural areas. However, village-level MSMEs continue to face various structural and operational challenges, including low levels of business legality, limited access to and utilization of digital technologies, and suboptimal product branding strategies. These constraints have led to reduced competitiveness of MSMEs in an increasingly competitive market environment. The Community Empowerment Learning Program (Kuliah Kerja Nyata–Pembelajaran Pemberdayaan Masyarakat, KKN-PPM) conducted by Universitas Gadjah Mada in Sendangtirto Village, Berbah Sub-district, Sleman Regency, was designed as a comprehensive effort to address these challenges. The program employed a participatory approach through socialization activities, training sessions, and direct assistance for MSME actors. Key activities included support for business legalization processes such as Business Identification Number (NIB) registration and halal certification, implementation of digital payment systems through QRIS, registration of businesses on digital platforms including Google Maps, Shopee Food, and online marketplaces, as well as training on product branding and digital literacy. The digital literacy component covered search engine optimization (SEO) and the utilization of artificial intelligence (AI) for promotional purposes. The results indicate an increased level of awareness among MSME actors regarding the importance of business legality, higher adoption of digital payment systems and online marketing platforms, and improvements in product branding strategies. Overall, the program contributed to enhancing the competitiveness of local MSMEs and strengthening the economic self-reliance of rural communities.